A Review of Research Methodologies Linking Green Supply Chain Practices and Green Supply Chain Performance - Gandhi, Mohd. Asif Indravadan; Sharma, Sanjay (International Journal of Supply Chain Management, 2014)
The objective of this paper is to explore the peer-reviewed literature on green supply chain practices and green supply chain performance with the intention of characterizing the research methodologies used in these areas of research. In line with this objective, the constructs “Green Supply Chain Practices” and “Green Supply Chain Performance” were identified. As indicated by the literature already published there seems to be certain set of methodologies which have mostly been used and that too frequently. Accordingly, there is a need to do a more detailed study that can pinpoint particular research methodologies that are usually used in research related to green supply chain practices and green supply chain performance. This paper attempts to achieve the aim by using a keyword search for identifying papers related to green supply chain practices and green supply chain performance. Finally the methodologies used are summarized in order of their usage in order to characterize the research methodologies used in linking green supply chain practices and green supply chain performance. This will help newer research work to flow in the right direction without reinventing the wheel and also it will act as a ready reference for newer research work to practicing managers.